Determination of elemental composition in Infant formula and growing up formula Among different brands available in Malaysia - Shafie, Wan Norfaezah Wan (Universiti Sains Malaysia, 2016)
The objective of this study was to determine the elemental compositions, including trace elements (copper, zinc, iron, manganese and selenium) and heavy metals (lead, cadmium and chromium) in infant and growing up formula among different brands locally available in Malaysia. Twelve different milk powder brands consisted each of six samples of infant formula and six samples of growing up formula were purchased and analyzed for elemental composition. Microwave digestion system was used for sample digestion and extraction. Flame Atomic Absorption Spectrometer (FAAS) was used to determine the elemental composition concentration. The trace elements in selenium (Se) for infants’ formula shows the highest concentrations followed by iron (Fe), zinc (Zn), copper (Cu) and manganese (Mn). There was a significant difference (p < 0.05) in concentration of Se, Fe, Zn, Cu, and Mn between the samples. Sample F (1.936 mg/L) was found to be the highest in Selenium concentration compared to other samples. In term of heavy metals, Cr was found to be the highest in concentration in infant formula, compared to Pb and Cd. Cd was not detected in some of the formulas. Sample C (0.080 mg/L) recorded the highest content of Chromium. There was also significant difference between trace elements in growing up formula. Iron and Selenium were found to be higher in growing up formula compared to copper, zinc and manganese. Between the samples, sample 3 (1.494 mg/L) recorded the highest in iron concentration, whereas Selenium was highest in sample 2 (1.991 mg/L) and sample 5 (1.991 mg/L). Lead was found to be the highest in concentration compared to other heavy metals in growing up formula, in which sample 5 (0.088 mg/L) had the highest amount compared to other samples. Although almost all of the trace elements and heavy metal shows significant amount in both growing up and infant formula, however there were still below the permissible limit for all of the elements except for lead, according to Food Act 1983 and Food Regulation 1985.